2010
DOI: 10.1177/193229681000400510
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Platelet-Rich Plasma to Augment Curative Diabetic Foot Surgery

Abstract: Autologous platelet-rich plasma (PRP) may enhance wound healing through the formation of a platelet plug that provides both hemostasis and the secretion of biologically active proteins, including growth factors such as platelet-derived growth factor, transforming growth factor (TGF)-β, TGF-β2, and epidermal growth factor. The release of these growth factors into the wound may create an environment more conducive to tissue repair and could accelerate postoperative wound healing. To our knowledge, there are no r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…There are studies related to the integration of these growth factors showing variety in order to imitate the natural environment of tissue formation, especially in tissue engineering research. In some studies, it was stated that PRP triggers neovascularization induction, angiogenesis, and granulation tissue formation via release of active protein biologically 29,30 . During the process of wound healing, VEGF increases neoangiogenesis by increasing vein permeability.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies related to the integration of these growth factors showing variety in order to imitate the natural environment of tissue formation, especially in tissue engineering research. In some studies, it was stated that PRP triggers neovascularization induction, angiogenesis, and granulation tissue formation via release of active protein biologically 29,30 . During the process of wound healing, VEGF increases neoangiogenesis by increasing vein permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The ischium and the superior soft Since then, PRP therapy has been effectively applied to many types of soft tissue repairs, and there are also many reports of its effectiveness in wound healing [9,10]. Platelets contain alpha granules that release several types of cytokines to promote wound healing, vascular synthesis, granulation, and epithelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the synergistic effect of a both autologous adipose tissue and PRP in a case study of a diabetic 65-year-old male patient who had a foot ulcer since 3 years [10]. Scimeca et al (2010) published the successful result for treatment of chronic plantar diabetic ulcer in a 49-year-old man using PRP [11]. A retrospective cohort of 599 patients with diabetic foot ulcers was published, and reported complete healing in 50% of patients undergoing PRP treatment and 41% of patients not treated with PRP [12].…”
Section: Discussionmentioning
confidence: 99%